Liquid biopsies using plasma exosomal nucleic acids and plasma cell-free DNA compared with clinical outcomes of patients with advanced cancers - Möhrmann, Lino; Huang, Helen J.; Hong, David S.; Tsimberidou, Apostolia M.; Fu, Siqing; Piha-Paul, Sarina A.; Subbiah, Vivek; Karp, Daniel D.; Naing, Aung; Krug, Anne; Enderle, Daniel; Priewasser, Tina; et al. (Clinical cancer research, 2017)
Purpose: Blood-based liquid biopsies offer easy access to genomic material for molecular diagnostics in cancer. Commonly used cell-free DNA (cfDNA) originates from dying cells. Exosomal nucleic acids (exoNAs) originate from living cells, which can better reflect underlying cancer biology. - Experimental Design: Next-generation sequencing (NGS) was used to test exoNA, and droplet digital PCR (ddPCR) and BEAMing PCR were used to test cfDNA for BRAFV600, KRASG12/G13, and EGFRexon19del/L858R mutations in 43 patients with progressing advanced cancers. Results were compared with clinical testing of archival tumor tissue and clinical outcomes. - Results: Forty-one patients had BRAF, KRAS, or EGFR mutations in tumor tissue. These mutations were detected by NGS in 95% of plasma exoNA samples, by ddPCR in 92% of cfDNA samples, and by BEAMing in 97% cfDNA samples. NGS of exoNA did not detect any mutations not present in tumor, whereas ddPCR and BEAMing detected one and two such mutations, respectively. Compared with patients with high exoNA mutation allelic frequency (MAF), patients with low MAF had longer median survival (11.8 vs. 5.9 months; P = 0.006) and time to treatment failure (7.4 vs. 2.3 months; P = 0.009). A low amount of exoNA was associated with partial response and stable disease ≥6 months (P = 0.006). - Conclusions: NGS of plasma exoNA for common BRAF, KRAS, and EGFR mutations has high sensitivity compared with clinical testing of archival tumor and testing of plasma cfDNA. Low exoNA MAF is an independent prognostic factor for longer survival. Clin Cancer Res; 24(1); 181-8. ©2017 AACR.